Dolgu Zeminlere Oturan Kıyı Yapısı Temellerinin Tasarımında Yeni Yöntemlerin İncelenmesi - Kılcı, Rıza Evren (Fen Bilimleri Enstitüsü, 2019)
Dolgu zeminlerde koruma tabakasının oturması yalnızca sismik yüklerden kaynaklanmayıp sismik yüke ek olarak akıntı etkisi, dalga etkisi, rüzgar yükleri kaynaklı yapısal salınım ve bunun benzeri titreşim etkileriyle deniz tabanında ve filtre tabakasında oluşabilen yukarı yönlü basınç gradyanları (hidrolik eğim) nedeniyle de oturmaların olabileceği anlaşılmaktadır. Ortaya çıkan bu yüksek basınç gradyanlarıyla, taban (çekirdek) malzemesi sökülebilmekte, hatta borulanma hadisesiyle tüm dolgu yapısında göçme yaşanabilmektedir. "Dolgu Zeminlere Oturan Kıyı Yapısı Temellerinin Tasarımında Yeni Yöntemlerin İncelenmesi" başlıklı bu tez çalışmasında yukarıda bahsedilen olguları ölçek etkilerini minimize ederek prototip ölçeğinde modelleyebilmek amacıyla yeni bir fiziksel model sistemi kurulmuştur. Oluşturulan bu fiziksel modelde ince kum, orta kum ve ince çakıl olmak üzere 3 çeşit zemin kullanılmış ve bu üç tip zemin için sonuçlar mukayese edilmiştir. Bu deney sisteminde "düşen basınç gradyanı" ve "salınımlı basınç gradyanı" altında iki farklı deney tipinde 65 adet deney yapılmıştır. Bu deney düzeneği, zemin içinden dışarıya doğru meydana gelen kararsız (zamanla değişen) basınç gradyanları nedeniyle yukarı yönlü sızma akımı ve borulanmanın hangi koşullarda meydana geldiğini daha derinlemesine inceleme fırsatı sunmuş ve böylece gerekli önlemlerin (filtre ve koruma tabakası) alınması yönünde olanak sağlamıştır. Tez çalışması 6 ana başlıktan oluşmaktadır. Bu başlıkları kısaca özetlemek gerekirse 1. başlık olan giriş bölümünde tezin amacı, konusu ve kapsamı ile yapılan tüm literatür çalışmaların kısa özeti sunulmuştur. 2. Bölümde, rüzgâr enerjisi ve açık deniz rüzgâr türbinleri başlıklı kısımda ilk olarak açık deniz rüzgâr enerjisinin Türkiye ve Dünyadaki yeri istatistiki şekiller aracılığıyla bakılmış, genel olarak açık deniz rüzgâr türbin tasarımı ve çeşitliliği özetlenmiştir. 3. Bölümde, türbin temellerinin tasarımında oyulma koruması ve deniz tabanının davranışının incelenmesi kısmında oyulma ve sıvılaşma kavramları kısaca anlatılmış, önemi üzerinde durulmuş ve yapılan literatür çalışmaları kısaca özetlenmiştir. 4. Bölümde, borulanma olgusunun tanımı ve koruma tabakası stabilitesi açısından incelenmesi başlıklı kısımda borulanma hadisesi anlatılmış ve geniş literatür araştırmasına yer verilmiştir. Yine bu bölümde dışa doğru basınç gradyanı etkisindeki filtre tabakalı ve tabakasız eğimli yüzeyde kuvvet dengesi ve su ile tane karışımının bir bütün olarak borulanma başlangıç kriterinin türetilmesi yapılmıştır. Elde edilen mevcut sonuçlar ile kararlı borulanma kriterlerinin karşılaştırılması yapılmış ve sonuçların uyum içerisinde olduğu görülmüştür. Ayrıca şevin filtre ile korunması durumunda borulanma kriteri olan formülasyon üzerinde değişik parametrelerin bir fonksiyonu olarak filtre tabaka kalınlığı ( Bf ) ile filtre taş kalınlığı (Df) arasında oranlamalar yapılarak grafikler üzerinde değerlendirmeler yapılmıştır. Bu bölümün son çalışmasında ise filtre tabakası altındaki bir zemin elemanını oluşturan su ve tane karışımının bir bütün olarak hareket edebilme ilkesinden farklı biçimde, zemin içerisindeki su ve zemin tanelerinin hareket denklemleri ayrı ayrı türetilmiştir. 5. bölümde salınımlı basınç gradyanı altında borulanma mekanizması deneyleri başlığı altında borulanma mekanizması deney düzeneği, kullanılan ölçüm aletleri ve deneyde kullanılan zeminlerin karakteristik özellikleri anlatılmıştır. 3 çeşit zemin ve iki farklı deney sistemiyle elde edilen deney sonuçları çizelgelerde gösterilmiş, yapılan deneylerde borulanma hadisesi görülmüş ise çizelgeye borulanma var, yok ya da limit durum (var) olarak yazılmıştır. Tüm deney sonuçları için basınç, basınç profili ve basınç gradyanı profili eğrileri tezin ekler bölümünde sunulmuştur. Tezin son bölümü olan 6. bölümde ise pratik uygulamalar için görüşler sunulmuş, tezin sonuç bölümü yazılmıştır. Bu tez çalışması kapsamında "Use of Steel Slag in Rubble – Mound Marine Structures", in proc. of 3rd Iron and Steel Symposium (UDCS'17), Karabuk, Turkey, 3-5 April 2017; Karabuk University, 2017,307-313. ve "A Modified Piping Criterion for Determination of Effective Filter Thickness under Revetment Slopes" 13th International Congress on Advances in Civil Engineering 12-14 September 2018, İzmir/Turkey 2 adet uluslararası bildiri ile Mechanism of Steady and Unsteady Piping in Coastal and Hydraulic Structures with a Sloped Face' Water, 2018, 10, 1757, 1 adet makale çalışması yapılmıştır. Ayrıca tez kapsamındaki çalışmalardan üretilen "Determination of Minimum Filter Thickness for Protection of Slopes against Piping" isimli bir makale de hazırlanma aşamasındadır.

In the case of embankment soil, the settlement is not only caused by the seismic loading. In addition to the seismic loading, the effects of currents and waves, as well as structural oscillation due to wind loading or similar vibration sources can be seen in the seabed, and particularly in the filter/armour layers placed to protect the structure foundation. Currents and waves cause high hydraulic gradients in both horizontal and vertical alignments. The particular interest of this study is the upward (or outward) directed pressure gradients effecting the subsoil and filters layers. With these potentially high pressure gradients, failure processes such the loss of fines from the base material (or subsoil), even the case of piping, can be experienced. For coastal and hydraulic structures, one of the most critical types of failure mechanisms to be experienced is undoubtedly piping. Piping is defined as the transport of the granular material through the cavities as a result of the flow or leakage of water driven by an outward directed hydraulic gradient (pressure gradient). The purpose of the current study is to investigate the mechanism of piping under steady and unsteady (i.e. oscillatory) hydraulic gradients. In this context, a physically consistent criterion for granular soils with inclined surfaces is formulated in order to determine the critical hydraulic gradient against piping. The advantage of this criterion is the inclusion of the friction forces as a resisting effect. For this purpose, force-balance is derived for an infinitesimal soil element which accounts for the driving forces (pressure gradient force) and resisting forces (self-weight of soil and friction forces). In this analysis, inertial terms were not taken into account. Once the analysis was performed for an infinitesimal soil element resting on a sloping surface without a filter layer, the obtained results were compared with the available data in the literature. The comparison yielded a general agreement showing that the obtained criterion can successfully represent the resisting friction forces. Subsequently, the approach was developed for sloping surfaces protected by a granular filter layer. The functionality of the formulation was demonstrated by means of a parametric study, and it was shown that this criterion is a viable method to obtain a minimum filter layer thickness. From this sense, this study is one of the rare studies in the literature which presents a tangible method for determination of the filter layer thickness for revetments. In the second part of the study, a group of experiments were performed to study the piping mechanism under unsteady hydraulic gradients. These experiments were designed for representing the effects that coastal structures are exposed as far as piping under wave action is concerned. Two types of unsteady hydraulic loads are considered for the experiments; (1) sudden loading, and (2) oscillatory loading. The originality of the designed setup stems from its capacity to simulate the driving forces in one-to-one scale in terms of magnitude and period. With this novel experimental setup, 65 experiments were conducted with the aforementioned two types of hydraulic loading. This experimental setup provided the opportunity to examine in more detail the upstream infiltration flow and the conditions under which the piping potentially occurs due to unsteady outward-directed pressure gradients. Three types of soils were used, each of which represents a different base soil condition. This way, a basis for comparison of different soil types was obtained. In the third, and the last, part of the study, one dimensional unsteady momentum equations are derived for the two phases of the soil, pore water and the grain group. The former equation has yielded a similar final formulation to the ones in the literature, whereas the latter equation is the first in the literature. The equation derived for the grain group provides a basis for calculation of dislocation of the soil grains in case piping occurs. The thesis consists of six main chapters. These chapters can briefly be summarized as follows. In the first chapter a brief summary of the purpose, subject matter and scope of the study are presented. In the second chapter, the structures of concern are presented with a special focus on offshore wind energy structures. In this context, onshore/offshore wind energy as well as offshore wind potential both in Turkey and in the world is discussed through statistical figures. In general, the design and diversity of offshore wind turbines are summarized. In the third chapter, the concept of seabed-structure-interaction, including the processes of scour and wave-induced seabed liquefaction, is discussed along with the perspective of scour protection for the seabed in the design of turbine foundations in the light of pertinent literature. In the fourth chapter, the description of piping phenomenon and the investigation of piping including cover layer stability are described, and a large literature survey is included. In this part of the thesis, the sloped face and the force balance of the mixture of water and grain as a whole are derived from the initial piping criterion. The comparison of the obtained results with the stable piping criteria was performed, and the results were seen to be in agreement. In addition, as a function of different parameters on the formulation with the sloped face filter, the ratio of the filter layer thickness to the filter layer stone size was derived as a parametric study, the results of which are presented as plots. In the last part of this chapter, the equations of motion of water and soil grains (as a group) are derived separately, unlike the principle of moving the mixture of water and grain forming a soil parcel under the filter layer as a whole. In the fifth chapter, under the heading of oscillatory pressure gradient, the mechanism of the piping under the heading of piping experiments, the measurement instruments used and the characteristics of the floors used in the experiment are described. The test results obtained with three different types of soil and two different types of hydraulic loading are presneted in the tables. Pressure values, pressure profiles as well as pressure gradient profiles for all conducted tests are presented in the appendix of the thesis. In the sixth chapter, the last chapter of the thesis, concluding remarks along with remarks on practical applications are presented. When the findings of the study are evaluated, it can be seen that the behavior of the subsoil under steady hydraulic gradient and unsteady hydraulic gradient is very different from each other. In case of unsteady loading, inertia terms will be effective, rendering the piping mechanism under steady and unsteady loadings different form each other. Hydraulic conductivity of the soil under unsteady hydraulic gradients becomes very important from piping point of view. Soils with low hydraulic conductivity are more susceptible to piping, a conclusion drawn from the currents study which is also expressed in the literature. When the experimental findings were examined, it was seen that the periods of oscillating pressure gradients did not have a significant effect on the results. In practical applications, the proper design of the filter layer as a precaution against piping is of great importance. In the design of coastal and marine structures, global climate change should be taken into account since the frequency and magnitude of the storms and other metocean events increase, also increasing the magnitude of pressure gradients in parallel. But there are still many vague points that further need to be clarified. In future studies, it is of great importance to make experimental studies and / or numerical modeling to determine the behavior of the filter layer under unsteady hydraulic loading situations. In these studies, more accurate approaches and design methods can be obtained by considering the factors such as inertia terms and soil elasticity. Within the scope of this thesis, three scientific papers have been published: (1) A conference paper titled "Use of Steel Slag in Rubble – Mound Marine Structures", in proc. of 3rd Iron and Steel Symposium (UDCS'17), Karabuk, Turkey, 3-5 April 2017; Karabuk University, 2017,307-313, (2) another conference paper titled "A Modified Piping Criterion for Analysis" presented in 13th International Congress on Advance in Civil Engineering 12-14 September 2018, Izmir / Turkey, and (3) an article ttiled "Mechanism of Steady and Unsteady Piping in Coastal and Hydraulic Structures with a Sloped Face" published in Water (2018, 10, 1757). In addition to these publications, an article entitled "Determination of Minimum Filter against Slopes against Piping" is underway.
Investigation Of New Methods In The Foundation Design Of Coastal Structures Placed On Embankments
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2019
Keywords: kıyı mühendisliği; kıyı koruma; tehlike azaltma; coastal engineering; shore protection; hazard mitigation